2019
DOI: 10.2217/rme-2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

Engineering, Differentiation and Harvesting of Human Adipose-Derived Stem Cell Multilayer Cell Sheets

Abstract: The study goals were to engineer and harvest scaffold-free undifferentiated/differentiated multilayer human adipose-derived stem cell (hADSC) cell sheets, in absence of treatment. Materials & methods: The hADSC are seeded in 35 mm culture dishes. At confluence or when multilayer cell sheets are formed, hADSC are treated with predefined differentiation culture media (adipocyte, chondrocyte and osteoblast). Results: Undifferentiated hADSC and differentiated adipocyte, osteoblast and chondrocyte hADSC multilayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Hamdi showed that grafting cells directly onto a heart damage area improved the heart functionality more, compared to injected single cells in the veins [123]. Different scaffolds can be considered as an option for an organ’s direct grafting of the MSC: Ceramic, collagen, hyaluronan [124] or none [125,126]. The scaffold should play a temporary role in grafting the cells onto the tissue, to let the normal tissue take over the scaffold when it degrades [127].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Hamdi showed that grafting cells directly onto a heart damage area improved the heart functionality more, compared to injected single cells in the veins [123]. Different scaffolds can be considered as an option for an organ’s direct grafting of the MSC: Ceramic, collagen, hyaluronan [124] or none [125,126]. The scaffold should play a temporary role in grafting the cells onto the tissue, to let the normal tissue take over the scaffold when it degrades [127].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…In addition to the thermoresponsive surface, other methodologies were developed to have the cell sheets in one piece: collagenase, amniotic membrane, electroresponsive/photoresponsive/pHresponsive/magnetic-responsive surface, and mechanical harvesting [94]. Instead of injecting single isolated cells, we have focused on engineering cell sheet with adipose stromal cells for different reasons, as explained in the introduction [95].…”
Section: Cell Sheet Technologymentioning
confidence: 99%
“…We have developed multilayer cell sheets, using adipose stromal cells [95]. Using specific cell culture conditions, the undifferentiated multilayer adipose stromal cell sheets have been engineered as well as differentiated cell sheets.…”
Section: Cell Sheet Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…A thermo-responsive surface can be used to collect a multilayer cell sheet, which can also be used for single-layer cell sheets. Other methodologies have been used for cell sheet harvesting, such as polyvinylidene di-fluoride membrane or Ethylene diamine tetraacetic acid, only for cell sheets with a strong cell-cell connection [9].…”
Section: Scaffold-free Strategymentioning
confidence: 99%